Application of Role Playing Methods in Improving Student Speaking Skills in Class V Indonesian Language Subjects SDN 526 Buntu Kamiri, Luwu Regency - Indri Pratiwi (Program Studi PGSD FIP UNM, 2021)
The problem of this research is the low learning outcomes of students' speaking skills in grade V SDN 526 Buntu Kamiri, Luwu Regency. The focus of this research is the application of role playing methods and improving students' speaking skills. As for the research subjects, 1 teacher of class V and 20 students of class V consisting of 12 girls and 8 boys. Data collection techniques through observation, tests, and documentation. The data analysis used was qualitative and quantitative analysis. The results showed that the teaching activities of the teacher in the first cycle were categorized as adequate and the first cycle of meeting 2 was categorized as good. Student learning activities in the first cycle of meeting 1 were categorized as adequate and the first cycle of meeting 2 was categorized as good. The improvement of the results of students 'speaking skills in the first cycle was in the good category, then in the second cycle the average score of the results of the students' speaking skills was in the good category (classical complete). The conclusion of this study is the role playing method can improve the speaking skills of students in class V SDN 526 Buntu Kamiri, Luwu Regency.Keywords: speaking skills, Role Playing Method